An environmental isolate of Pseudomonas, 20EI1, reduces Aspergillus flavus growth in an iron-dependent manner and alters secondary metabolism - Wyman, Elizabeth M.; Grayburn, W. Scott; Gilbert, Matthew K.; Lebar, Matthew D.; Lohmar, Jessica M.; Cary, Jeffrey W.; Sauters, Thomas J. C.; Rokas, Antonis; Calvo, Ana M. (Frontiers in Microbiology, 2025)
IntroductionAspergillus flavus is an opportunistic pathogenic fungus that infects oilseed crops worldwide. When colonizing plants, it produces mycotoxins, including carcinogenic compounds such as aflatoxins. Mycotoxin contamination results in an important economic and health impact. The design of new strategies to control A. flavus colonization and mycotoxin contamination is paramount.MethodsThe biocontrol potential of a promising new isolate of Pseudomonas spp., 20EI1 against A. flavus was assessed using bioassays and microscopy. To further elucidate the nature of this bacterial-fungal interaction, we also performed chemical and transcriptomics analyses.ResultsIn the present study, Pseudomonas spp., 20EI1 was able to reduce the growth of A. flavus. Furthermore, we determined that this growth inhibition is iron-dependent. In addition, Pseudomonas 20EI1 reduced or blocked the production of aflatoxin, as well as cyclopiazonic acid and kojic acid. Expression of iron-related genes was altered in the presence of the bacteria and genes involved in the production of aflatoxin were down-regulated. Iron supplementation partially reestablished their expression. Expression of other secondary metabolite (SM) genes was also reduced by the bacteria, including genes of clusters involved in cyclopiazonic acid, kojic acid and imizoquin biosynthesis, while genes of the cluster corresponding to aspergillicin, a siderophore, were upregulated. Interestingly, the global SM regulatory gene mtfA was significantly upregulated by 20EI1, which could have contributed to the observed alterations in SM.DiscussionOur results suggest that Pseudomonas 20EI1 is a promising biocontrol against A. flavus, and provide further insight into this iron-dependent bacterial-fungal interaction affecting the expression of numerous genes, among them those involved in SM.